The National Health Service - Great Britain. Central Office of Information. (London : His Majesty's Stationery Office, 1948)
1948 1948 1940s 38 pages while the regional boards which appoint the latter are also represented on the teaching hospital boards. By this system of cross-representation, and with support from the Ministry of Health, teamwork on a new scale is now made possible. Circumstances will no longer compel the leaders of the medical profession largely to confine their influence to the universities, the teaching hospitals, the largest cities, or the individual hospitals with which they are connected. The Task Before the Hospital All that is medically necessary for a patient, as has already been stated, is provided without charge by the hospital and specialist services when the patient requires it. Usually — that is, apart from emergency — he is put in touch with them by, and on the advice of, his family doctor. The first duty of the hospital and specialist services is to help the patient by helping his doctor when the doctor asks for advice or skilled support. In most cases patients requiring to be seen by a hospital specialist will visit the hospital out-patient department for this purpose. Quite often special clinics will be held in other places (such as clinics for venereal disease and tuberculosis) ; or specialists will hold regular sessions at the welfare clinics of local authorities and at health centres. In all these clinics patients can be examined by experts at the request of their family doctors ; in many of them X-rays, and other aids to diagnosis which the family doctor does not possess, can be brought into action. In addition to providing accommodation for in-patients requiring specialist care there are many hospitals in which facilities will be available for patients to be admitted for treatment by their own family doctors. Treatment by the specialist service includes the provision of any appliances, such as artificial limbs or the Government's new hearing aids, necessary for fitness. The patient is free to use any branch of the Service without using all of it, just as the doctor or dentist is free to work partly in the Service and partly outside. In seeking expert help for his patient the family doctor is not tied to hospitals and specialists either of his own district or his own region. 'Free' Patient and Paying Patient As far as is humanly possible in present hospital conditions, the hospital patient who must for medical reasons have privacy will be given it ; the aim is to ensure accommodation in small wards or single rooms for all who need it for medical reasons and for as many as possible who would prefer it for other reasons. In a great many hospitals this cannot be done today ; the design of the buildings will not permit it, and there are not enough beds and nurses. But in hospitals 15 21/1489